2008
DOI: 10.1128/jb.01080-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Involved in Inversion of Stereochemistry of a C-12 Hydroxyl Group in the Catabolism of Cholic Acid by Comamonas testosteroni TA441

Abstract: Comamonas testosteroni TA441 degrades steroids such as testosterone via aromatization of the A ring, followed by meta-cleavage of the ring. In the DNA region upstream of the meta-cleavage enzyme gene tesB, two genes required during cholic acid degradation for the inversion of an ␣-oriented hydroxyl group on C-12 were identified. A dehydrogenase, SteA, converts 7␣,12␣-dihydroxyandrosta-1,4-diene-3,17-dione to 7␣-hydroxyandrosta-1,4-diene-3,12,17-trione, and a hydrogenase, SteB, converts the latter to 7␣,12␤-dih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
49
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 20 publications
(26 reference statements)
0
49
0
Order By: Relevance
“…This could be the reason for the fact that strain R1 is not able to grow with cholate as the sole carbon source, despite its ability to release one acetyl-CoA residue from the substrate (19). The propionyl residue was further degraded via the methylcitric acid cycle, which is supported by the fact that all genes for this pathway are present in the genome of strain Chol1, while those for the methylmalonyl-CoA pathway are not (32).…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…This could be the reason for the fact that strain R1 is not able to grow with cholate as the sole carbon source, despite its ability to release one acetyl-CoA residue from the substrate (19). The propionyl residue was further degraded via the methylcitric acid cycle, which is supported by the fact that all genes for this pathway are present in the genome of strain Chol1, while those for the methylmalonyl-CoA pathway are not (32).…”
mentioning
confidence: 55%
“…The function of this specificity for the reduction of HADT is not known. In C. testosteroni, the formation of 12␤-DHADD is necessary for the subsequent hydroxylation at C-9 and the formation of THSATD (32). The same might be true for strain Chol1, because 12␤-DHADD, the end product of anaerobic cholate degradation, is immediately transformed into THSATD by cell suspensions upon aeration (15).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…strain Chol1. In the former strain, genes responsible for oxidation of the steroid nucleus were found (10)(11)(12)(13), while in the latter, genes responsible for degradation of the cholate side chain were identified, including acad, encoding an acyl coenzyme A (acyl-CoA) dehydrogenase (2), and skt, encoding a thiolase (3).…”
mentioning
confidence: 99%
“…The main intermediate compounds in bacterial steroid degradation were identified from the 1950s through the 1980s, and the mechanism of steroid degradation was predicted on the basis of the compounds identified for the purpose of obtaining medical materials (1)(2)(3)(4)(5)(6)(7)(8)(9). The degradation genes have been known since approximately 1980 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), but the details of the degradation had remained unclarified, until we revealed the degradation mechanism of the A and B rings of the core steroidal structure (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Our studies have suggested that an approximately 100-kb DNA region in C. testosteroni TA441 is a large steroid degradation gene cluster (Fig.…”
mentioning
confidence: 99%